2018
DOI: 10.7717/peerj.5875
|View full text |Cite
|
Sign up to set email alerts
|

Canadian packaged gluten-free foods are less nutritious than their regular gluten-containing counterparts

Abstract: BackgroundA strict gluten-free (GF) diet is required for the management of celiac disease (CD). The nutritional adequacy of this diet has been questioned due to the elimination of wheat, an important vehicle for micronutrient fortification and source of fibre. While novel and/or reformulated packaged GF products have rapidly entered the marketplace, providing alternatives to wheat-based staples, it is unknown whether these new products are nutritionally comparable.MethodsFrom a database of 3,851 foods collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 18 publications
5
29
0
Order By: Relevance
“…In contrast, 25.4% could be labeled as a source of fiber [21,22]. Compared to other recent studies, our food composition database showed similar or slightly lower nutrient values than others [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…In contrast, 25.4% could be labeled as a source of fiber [21,22]. Compared to other recent studies, our food composition database showed similar or slightly lower nutrient values than others [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 41%
“…Further studies are nevertheless required to investigate the micronutrient content of GF food products, since very few reported data exist. Kulai and Rashid [37] and Jamieson et al [26] informed of a significant lower iron and folate content in GF products compared to gluten containing food. Potassium content was also significantly lower in GF food products [27].…”
Section: Discussionmentioning
confidence: 99%
“…Others were afraid that the GF products are unhealthy. Studies comparing the nutritional quality of GF products with their GC counterparts show that GF products contain more salt, sugar and saturated fats and less fibre and protein compared to their GF counterparts [ 11 , 12 , 23 ]. A similar study is currently ongoing in Norway, as there are currently no published data on the nutritional quality of Norwegian GF products.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study among 17 adults diagnosed with CD in Canada concluded that the sole medical recommendation of a GF diet fails to acknowledge the difficulties those with CD can endure in the current GF landscape [ 7 ]. Studies show that GF products are more expensive than their GC counterparts [ 8 10 ] and that GF products often have a lower nutritional quality than their GC equivalents [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…With gluten withdrawal, refined ingredients, with high glycemic indexes, are used to achieve desirable sensory characteristics, not prioritizing the nutritional aspects [14,18,24]. This tendency has been verified in most studies regarding gluten-free bread using higher fat and carbohydrates contents and presenting high GIs [14,27,28]. Gluten-free bread tends to be high in lipids and additives (mainly gums and fibers) in addition to starches.…”
Section: Introductionmentioning
confidence: 99%